Analysis of Scholarship Program for Strengthening the Reforming Institution BPKP - Tjiptadi; Mohammad Sofyan; Soleh; Deni Sutisna (Yayasan Ilomata, 2020)
The purpose of the Scholarship Program for Strengthening the reforming institution (SPIRIT) is to build the capacity of participating institutions by (i) strengthening human resources in critical functional areas; and (ii) improving their ability to start and manage reforms. The study showed that the Transfer of Knowledge by the SPIRIT Alumni in the Unit of work could not be measured objectively. Transfer Knowledge conducted by SPIRIT alumni is generally informally to complete the work is judged to have a relatively high difficulty level of SPIRIT Alumni are usually able to apply their knowledge and skills with teammates/colleagues in their units.